Evaluation of E-school applications as a management information system - Polat, Murat; Arabaci, I. Bakir (Ankara University, 2013)
The purpose of the study is to determine the perceptions of the teachers and principals of primary schools in Muş Province of Turkey on the status of the existing competence of e-school as a management information system and to make an assessment of the e-school management information system.This study was designed as a survey study. The population comprises of 1698 teachers and school principals working in the state primary schools in the central district of Muş province during the 2010-2011 educational year. The sample consists of 835 randomly selected teachers and school principals. The results showed that there is not a statistically significant difference between the perceptions of the majority of the teachers and the school principals who think that the e-school system is adequate in terms of institutional affairs, student affairs and student report card works period. On the other hand, there is a statistically significant difference regarding the teachers' and school principals' perceptions of the favorite place of access to e-school and adequacy of the e-school system.
Yönetim bilgi sistemi olarak e-okul uygulamalarının de?erlendirilmesi
Keywords: E-school; Management information system; Ministry of national education